Analysis of intravitreal using of anti vegf-medications for diseases of fundus accompanied by exudation and neovascularization - N. G. Zavgorodnya; I. A. Poplavska; S.L. Shevluk; D.V. Martynov (Zaporozhye State Medical University, 2013)
Nowadays, new methods of treatment of choroidal neovascularization are being actively developed and introduced in exudative form of age-related macular degeneration (AMD), complicated myopia, diabetic retinopathy and post-thrombotic retinopathy. Medications that block vascular endothelial growth factor (VEGF), which is the main link in the pathogenesis of retinal neovascularization and hyperfiltration, have become widespread. It is known that damage of endothelial cells of retinal vessels occurs in consequence of oxidative stress that leads to the death of pericytes, hyperfiltration of plasma from the vascular bed, hemorrhages and retinal hypoxia. The intracellular concentration of specific protein that regulates the transcription of genes (HIF-1) increases in response to hypoxic damage in the cells of the retina, which leads to increased transcription of the VEGF gene, which acts directly on the epithelium providing regeneration, stimulating the proliferation and neovascularization. Considering this, anti-VEGF medications have found their application in the treatment of choroidal neovascularization in clinical practice. Today, two preparations that block VEGF: selective (pegaptanib) and non-selective (ranibizumab) are used mostly common. The purpose of this investigation was to study the effectiveness of anti-VEGF medications in patients with choroidal neovascularization of different genesis. The analysis presents the results of 50 patients (50 eyes) treatment with choroidal neovascularization on the background of various diseases of the retina. Pegaptanib ("Macugen") was used for the treatment of 35 patients (35 eyes), the rest (15 eyes) - ranibizumab ("Lucentis"). According to fluorescein angiography the subretinal neovascular membrane was in the stage of activity in all eyes. The effectiveness of the treatment was assessed by visometry, ophthalmoscopy, optical coherence tomography and fluorescein angiography. Application of intravitreal injection of pegaptanib improves visual acuity in 66% of cases in patients with choroidal neovascularization and exudation, application of ranibizumab - in 60% of cases. According to optic coherence tomography reduction of the retina thickness after injection of pegaptanib into the vitreous body is achieved in 57%, after ranibizumab - in 47% of cases, the suppression of activity of subretinal neovascular membrane by results of fluorescein angiography - in 26% and 27% respectively. The application of both selective and non-selective anti-VEGF medications renders substantial positive effect in patients with choroidal neovascularization and exudation, and it is safe and promising direction in treatment of this group of patients. So, in most cases using of pegaptanib and ranibizumab promotes the improvement or stabilization of visual functions and regression of neovascularization and exudation in patients with choroidal neovascularization and exudation of different genesis. This method of treatment is safe, however, it requires further studying, particularly in patients after repeated using of the anti-VEGF medications.